Is it cystic fibrosis? The challenges of diagnosing cystic fibrosis. (August 2019) - Simmonds, N.J.
Abstract: The spectrum of conditions caused by abnormal CFTR function is broad – from 'classic' cystic fibrosis (CF) to single organ conditions termed CFTR-related disorders. Defining and securing the diagnosis in an important minority of patients can be a challenge as the sweat test is equivocal or normal; the impact this has on the patient (at different stages of their life) can be very significant as it has the potential to lead to misdiagnosis and over (or under) treatment with associated psychological burden. The nasal potential difference test and intestinal current measurements are physiological measurements of CFTR function and thus can provide important diagnostic information. This article provides an overview of the latest developments in CF diagnostics, outlining the approach to be taken when the diagnosis is unclear and some of the areas of uncertainty.